2020
DOI: 10.23889/ijpds.v5i1.1346
|View full text |Cite
|
Sign up to set email alerts
|

Identifying children with Cystic Fibrosis in population-scale routinely collected data in Wales

Abstract: Introduction The challenges in identifying a cohort of people with a rare condition can be addressed by routinely collected, population-scale electronic health record (eHR) data, which provide large volumes of data at a national level. This paper describes the challenges of accurately identifying a cohort of children with Cystic Fibrosis (CF) using eHR and their validation against the UK CF Registry. Objectives To establish a proof of principle and provide insight into the merits of linked da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The similarity-based approach that we have developed re-used a comprehensive phenotypic description of patients based on their EHR data to detect ciliopathy patients in a clinical data warehouse. Unlike other studies using only a limited set of features presented in EHR, such as International Classification of Disease (ICD) codes (Griffiths et al, 2020), or a set of predefined disease specific phenotypes (Savolainen et al, 2021), we extracted all UMLS medical concepts in EHRs. Our results showed that the performance can be improved by including more phenotypes (6296 vs. 1578 phenotypes).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity-based approach that we have developed re-used a comprehensive phenotypic description of patients based on their EHR data to detect ciliopathy patients in a clinical data warehouse. Unlike other studies using only a limited set of features presented in EHR, such as International Classification of Disease (ICD) codes (Griffiths et al, 2020), or a set of predefined disease specific phenotypes (Savolainen et al, 2021), we extracted all UMLS medical concepts in EHRs. Our results showed that the performance can be improved by including more phenotypes (6296 vs. 1578 phenotypes).…”
Section: Discussionmentioning
confidence: 99%